2019
DOI: 10.5209/mbot.60127
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical investigation of 'Chamaerops humilis' in the area of Beni Snous (Western of Algeria)

Abstract: The ethnobotanical potentials of Chamaerops humilis in the Béni Snous region (south-west of Tlemcen, western Algeria) has been studied to know the therapeutic utilities and the practices of the local populations, in order to valorize this resource. A series of ethnobotanical surveys were carried out using a questionnaire on the 3 municipalities of Beni Snous (Beni Bahdel, Azail, and Beni Snous). The frequency of use of Chamaerops humilis in the region of study is closely related to the profile of the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
4
9
0
Order By: Relevance
“…Our results corroborate with other ethnobotanical surveys done at the national level such as an ethnobotanical study conducted in the High Moulouya which proved that the dominant users of traditional medicine are illiterate people with a percentage of 41% [ 75 ]. Our results are also in agreement with other studies and ethnobotanical surveys conducted in Algeria such as Medjati who found that there is a correlation between the level of study and the medicinal use of Chamaerops humilis between illiterate people, primary-level people, secondary-level people, and university-level people with percentages of 96.7%, 89.2%, 83%, and 58.9%, respectively, [ 16 ]. Other studies were conducted nationwide, such as that of Mehdioui and Kahouadji who showed that the vast majority of users of medicinal plants are illiterate, with a percentage of 66% followed by people with a primary level with 26%, while those with secondary and university levels of education use very little medicinal plants (secondary 7%, university 1%) [ 69 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results corroborate with other ethnobotanical surveys done at the national level such as an ethnobotanical study conducted in the High Moulouya which proved that the dominant users of traditional medicine are illiterate people with a percentage of 41% [ 75 ]. Our results are also in agreement with other studies and ethnobotanical surveys conducted in Algeria such as Medjati who found that there is a correlation between the level of study and the medicinal use of Chamaerops humilis between illiterate people, primary-level people, secondary-level people, and university-level people with percentages of 96.7%, 89.2%, 83%, and 58.9%, respectively, [ 16 ]. Other studies were conducted nationwide, such as that of Mehdioui and Kahouadji who showed that the vast majority of users of medicinal plants are illiterate, with a percentage of 66% followed by people with a primary level with 26%, while those with secondary and university levels of education use very little medicinal plants (secondary 7%, university 1%) [ 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…In Algeria, according to a survey conducted by Medjati et al, the heart of palm and spadices are used against gastrointestinal diseases and the fruits as antiseptic, the roots are used in decoction against intestinal worms and as a treatment for anemia, they are also used in women for cleaning the uterus after childbirth, and the leaves are used against gastrointestinal attacks and hepatitis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This category of people is interested in plants not only through scientific information, but they are also good users who acquire their knowledge through their ancestors and their families (Sari et al, 2014). Women are better acquainted with medicinal plants; this is due in particular to the exchanges, which unite them, and to the oral transmission which is made from generation to generation (Benkhnigue et al, 2011;Medjati et al, 2019). The practice of traditional medicine is more pronounced among married people than single people, which is related to the fact that the use of plants is of much greater interest to households, who use these plants to give first aid to their children (El hafian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…By far most of the information is still in the hands of customary healers and data of healers is either lost or go to age by the verbal. In this manner, the ethnobotanical examination tries to report the information of the healers with a specific end goal to save it for some time later (Seifu, 2004;Boucherit et al, 2017;Medjati et al, 2019). Botanical collection of the related ethno-organic information ought to be done before such rich legacies are lost because of different anthropogenic and other characteristic causes (Martin, 1995).…”
Section: Introductionmentioning
confidence: 99%